Ada (2017)
Ada is an emotional therapy that arises from the need found from the knowledge of women in the different stages of cancer (diagnosis, treatment and survival). The opportunity that gives value to the project lies in the empowerment of patients so that they become their own therapists in the emotional field. The above, based on different theories that take the good mood as a starting point for a better quality of life and in some cases, a possible cure. In this way, magical thinking appears as a powerful tool that patients can use, individually, to achieve this spiritual empowerment in times of crisis.